Exploring Student Engagement Patterns in English Utilizing Learning Management System Platform: An Empirical Analysis - Futwi Larasati (STAI Hubbulwathan Duri, 2023)
Student engagement is a crucial component of learning, particularly when using Learning Management Systems (LMS) in educational institutions. The adoption of LMS is on the rise, and Senior High School in Demak is no exception, as it has implemented an LMS to facilitate technology-based learning. This study aims to investigate student engagement in the Learning Management System, specifically in English classes. The purpose of this study is to examine student engagement in the Learning Management System, with a focus on tenth-grade students who are adjusting to their new academic environment. The study's objective is to explore the extent to which students are engaged when using the LMS. This research employs a descriptive qualitative method with theoretical analysis derived from Fredricks et al. (2004), which categorizes engagement into behavioral, emotional, and cognitive domains. The study focuses on a sample of 36 students from the third social class. This descriptive qualitative research employed three instruments for collecting the data. Those are observation, questionnaire, and interview. The findings reveal that students exhibit a range of engagement levels when using the LMS, with most students showing positive engagement. However, there are areas where engagement could be improved. Additionally, the LMS provides students with several benefits that aid their daily learning. This research enriches our understanding of student engagement when using LMS, specifically in English classes. The study's results demonstrate that while most students exhibit positive engagement, there is room for improvement. Overall, this study highlights the importance of student engagement in LMS and suggests ways to enhance it.